Synergistic effect of polyacrylamide (PAM) and silica on the rheological performance of water-based drilling fluid at specific temperature / Jin Kwei Koh ... [et al.] - Kwei Koh, Jin; Wei Lai, Chin; Johan, Mohd Rafie; Seng Gan, Sin; Chua, Wei Wei (2022)
The rheological performance of drilling fluid in bored pile operation is the most concerning issue for the geotechnical field. Usually, polymer is a common additive used in a bored pile operation as it works well in operational, environmental, and economic aspects. High molecular weight with good gelling behaviour polyacrylamide (PAM) were used in this study as it is eco-friendly, though it is temperature-sensitive during the drilling operation. Thus, the hybridisation of silica is required in PAM-based drilling fluid. The study investigated the effects of specific temperatures on PAM and modified PAM.